Early human social transmission during Marine Isotope Stage 5: a perspective from the Kalahari Basin - Maenzanise, Precious (Department of Archaeology, 2025)
The social transmission of cultural information is widely recognized as a crucial component contributing to the survival and prosperity of our species. This thesis studies lithic technological systems to assess the extent of the transmission of cultural information between different early human groups across the Kalahari Basin and adjoining regions during Marine Isotope Stage (MIS) 5 (~130-74 ka), a key time and place for understanding the emergence and expansion of complex behaviors in Africa. It has been proposed that glacial periods (e.g., MIS 4) in southern Africa were characterized by coalescence, while interglacial periods (e.g., MIS 5) were characterized by population fragmentation. While these previous hypotheses represent important examples for testing the degrees of population interconnectedness during MIS 5, they were based primarily on sites outside of the Kalahari Basin and its environs. Therefore, the central inquiry of this thesis is to investigate the presence and extent of cultural transmission among hunter-gatherer populations in and around the Kalahari Basin, assessing whether patterns of population fragmentation observed during MIS 5 are discernible in these regions. This inquiry is achieved by studying lithic assemblages from multiple sites and comparing them using a behavioral approach to cultural transmission. The samples studied are from Ga-Mohana Hill North Rockshelter, Kathu Pan 6, Erfkroon, and Florisbad in South Africa, and ≠Gi and White Paintings Rockshelter in Botswana. The results of this study indicate there are many technological similarities across most of the studied sites, including the predominant use of local raw materials, recurrent Levallois methods, hard hammer percussion technique, core maintenance primarily by débordant removals, manufacturing of similar products, mostly with faceted platforms, and a low frequency of formal tools. This homogeneity may reflect technological information exchange and connections between human groups at these sites. The connectivity is inferred to be closely linked to their adaptation to the drier climatic conditions that persisted in the Kalahari Basin and its adjoining regions, in contrast to coastal and other inland areas. The arid and semi-arid environments may have necessitated the formation of social ties to access scarce and potentially unpredictable resources. In contrast to some other regions that show fragmentation during interglacial periods, the Kalahari Basin and adjacent regions did not follow the same pattern.